Effect of the "universal test and treat" policy on the characteristics of persons registering for HIV care and initiating antiretroviral therapy in Uganda - Levicatus Mugenyi; Christian H. Hansen; Christian H. Hansen; Philippe Mayaud; Philippe Mayaud; Janet Seeley; Janet Seeley; Robert Newton; Mastula Nanfuka; Andrew Abaasa; Kenneth Mugisha; Michael Etukoit; et al. (Frontiers Media S.A., 2023)
We examined the effect of the Universal Test and Treat (UTT) policy on the characteristics of people living with HIV (PLHIV) at enrolment in HIV care and initiation of antiretroviral therapy (ART) in Uganda using data from 11 nationally representative clinics of The AIDS Support Organisation (TASO). We created two retrospective PLHIV cohorts: pre-UTT (2004-2016), where ART initiation was conditional on CD4 cell count and UTT (2017-2022), where ART was initiated regardless of World Health Organisation (WHO) clinical stage or CD4 cell count. We used a two-sample test of proportions and Wilcoxon rank-sum test to compare proportions and medians, respectively, between the cohorts. A total of 244,693 PLHIV were enrolled at the clinics [pre-UTT, 210,251 (85.9%); UTT, 34,442 (14.1%)]. Compared to the pre-UTT cohort, the UTT cohort had higher proportions of PLHIV that were male (p < 0.001), aged 18-29 years (p < 0.001), aged >69 years, never married (p < 0.001), and educated to primary (p < 0.001) and post-primary (p < 0.001) school level at enrolment in HIV care and ART initiation. Overall, 97.9% of UTT PLHIV initiated ART compared to 45.2% under pre-UTT. The median time from enrolment in HIV care to ART initiation decreased from 301 [interquartile range (IQR): 58-878] pre-UTT to 0 (IQR: 0-0) under UTT. The median CD4 count at ART initiation increased from 254 cells/μL pre-UTT to 482 cells/μL under UTT (p < 0.001). Compared to the pre-UTT cohort, the UTT cohort had higher proportions of PLHIV with a CD4 count >500 cells/μL (47.3% vs. 13.2%, p < 0.001) and WHO stage 1 (31.7% vs. 4.5%, p < 0.001) at ART initiation. Adoption of the UTT policy in Uganda was successful in enrolling previously unreached individuals, such as men and younger and older adults, as well as those with less advanced HIV disease. Future research will investigate the effect of UTT on long-term outcomes such as retention in care, HIV viral suppression, morbidity, and mortality.